25 years of the Rome Statute: paradigmatic challenges in their implementation - Ramos Borges, Osnarci Rafael (2025)
After more than two decades since the creation of the International Criminal Court, progress has been made in the field of International Criminal Justice, however, such institution is exposed to the paradox of what it is versus what is wanted from it. This article addresses as its central thesis the lack of uniformity of criteria in the adoption of measures that integrate International Criminal Law in the domestic legal systems of the States Parties that have a system of Continental Law to respond to these trials of public opinion in which it is regularly involved. It also examines how, in the absence of integration, the principles of complementarity and cooperation are undermined, making it impossible to improve the Court’s effectiveness. Finally, it addresses recommendations to reduce the impunity gap in the face of the new decade that lies ahead to maintain peace, security, and the well-being of humanity.